Transformasi Nilai Dakwah Menjadi Strategi Brand Loyalty di Lembaga Pendidikan Pesantren - Sofia; Moch Hafiduddin (Educational Research Center, 2025)
This study focuses on the transformation of Islamic da'wah values into brand loyalty strategies within Islamic educational institutions based on modern pesantren. The main objective is to examine how core da'wah values such as shiddiq (honesty), amanah (responsibility), tabligh (value transmission), and ukhuwah islamiyah (Islamic brotherhood) are internalized into the institutional system and communication strategies of Madrasah Aliyah (MA) Sullamul Hidayah in Probolinggo. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations, and document analysis, then analyzed using thematic analysis. The findings reveal that da'wah values are concretely integrated into managerial and institutional communication practices, fostering emotional and spiritual loyalty among students and parents. This strategy aligns with a value-based marketing approach, in which loyalty is built not only on the technical quality of educational services but also on the alignment of shared values perceived by education consumers. The study contributes to Islamic educational management theory by introducing the concept of da'wah-based brand loyalty. Practically, it implies that Islamic educational institutions should adopt da'wah values as the foundation for their policies and service strategies to build long-term trust and attachment with the community.